2016
DOI: 10.1364/ol.41.004534
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient singular surface plasmon generation by achiral apertures

Abstract: We report a highly efficient generation of singular surface plasmon (SP) field by an achiral plasmonic structure consisting of Λ-shaped apertures. Our quantitative analysis based on leakage radiation microscopy (LRM) demonstrates that the induced spin-orbit coupling can be tuned by adjusting the apex angle of the Λ-shaped aperture. Specifically, the array of Λ-shaped apertures with the apex angle 60• is shown to give rise to the directional coupling efficiency. The ring of Λ-shaped apertures with the apex angl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…This approach rigorously involves the nonparaxial light propagation and geometrical aberration in the microscope, which have to be considered for an accurate description of the imaging process [27,28]. To simulate the reversible SH effect for a metasurface formed by an array of 4 × 4 nanoantennas, we thus consider 16 pairs of orthogonal in-plane dipoles (oriented perpendicularly to each arm of the -shaped antennas) and coherently sum their electric fields as a function of the imaging direction [10,20,29]. The interactions between each dipole are fairly neglected as assumed in [29].…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach rigorously involves the nonparaxial light propagation and geometrical aberration in the microscope, which have to be considered for an accurate description of the imaging process [27,28]. To simulate the reversible SH effect for a metasurface formed by an array of 4 × 4 nanoantennas, we thus consider 16 pairs of orthogonal in-plane dipoles (oriented perpendicularly to each arm of the -shaped antennas) and coherently sum their electric fields as a function of the imaging direction [10,20,29]. The interactions between each dipole are fairly neglected as assumed in [29].…”
Section: -4mentioning
confidence: 99%
“…To simulate the reversible SH effect for a metasurface formed by an array of 4 × 4 nanoantennas, we thus consider 16 pairs of orthogonal in-plane dipoles (oriented perpendicularly to each arm of the -shaped antennas) and coherently sum their electric fields as a function of the imaging direction [10,20,29]. The interactions between each dipole are fairly neglected as assumed in [29]. The intensity and polarization associated with the total electric field is presented in Fig.…”
Section: -4mentioning
confidence: 99%
“…It is worth mentioning that our experimental approach allows the determination of the complex value of β, that is the relative weight of the minor dipole amplitude with respect to the major dipole. Recently, we demonstrated that the aspect ratio of the slit is critical for the design of nanostructures with optimized plasmonic coupling and directivity efficiency. , Notably, we used leakage radiation microscopy on a thin metal film , in order to quantify the contribution of each dipole in the SP generation. However, only partial information on the relative weight of the minor axis dipole, that is its real part, was accessed.…”
mentioning
confidence: 99%